Interaction of tick-borne encephalitis virus with host and vector cells - Tykalová, Hana (Jihočeská univerzita, 2022)
The proposed thesis deals with the various aspects of tick-borne encephalitis virus infection in the host and the vector on the cellular level. It uncovers transcriptomic and proteomic responses in infected cells in the human neurons and astrocytes, and vector cells. It identifies the subgenomic flaviviral RNA as an important pathogenesis effector that can interfere with the vector RNAi pathway, and at the same time denotes the components of this pathway. It also describes the phenomenon of impairment of host protein and rRNA synthesis upon TBEV infection. Moreover, it uncovers the importance of quasispecies in the adaptation to vector and host cells.
Interaction of tick-borne encephalitis virus with host and vector cells
Keywords: tick-borne encephalitis virus; tick cells; neural cells; immune response; RNAi pathway; translational shut-off; transcriptional shut-off; quasispecies; transcriptomic; proteomics; tick-borne encephalitis virus; tick cells; neural cells; immune response; RNAi pathway; translational shut-off; transcriptional shut-off; quasispecies; transcriptomics; proteomics